2020
DOI: 10.1016/j.jos.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hip kinematics before and after periacetabular osteotomy in patients with dysplasia

Abstract: Background: We prospectively analyzed the hip kinematics in patients with developmental dysplasia of the hip (DDH) before and after periacetabular osteotomy (PAO) and in healthy subjects while squatting to determine the influence of coverage of the femoral head on hip kinematics. Methods: 14 hips in 14 patients with DDH and 10 hips in 10 volunteers were included. Continuous radiographs while squatting and computed tomography images were obtained to assess the in vivo kinematics of the hip and the rim-neck dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Therefore, the present study utilized a 3D‐to‐2D model image registration technique to measure rotational alignment from radiographs taken in both the supine and standing positions. This technique has been previously used to analyse hip and knee joint kinetics using fluoroscopic images of daily activities, such as walking and squatting, demonstrating its high accuracy [ 9 , 25 , 46 ]. It has recently been applied to assess changes in axial alignment between the supine and standing positions in patients after total hip arthroplasty [ 42 ] or the intraoperative acetabular component in total hip arthroplasty [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study utilized a 3D‐to‐2D model image registration technique to measure rotational alignment from radiographs taken in both the supine and standing positions. This technique has been previously used to analyse hip and knee joint kinetics using fluoroscopic images of daily activities, such as walking and squatting, demonstrating its high accuracy [ 9 , 25 , 46 ]. It has recently been applied to assess changes in axial alignment between the supine and standing positions in patients after total hip arthroplasty [ 42 ] or the intraoperative acetabular component in total hip arthroplasty [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The computational bone collision simulations in the study by Steppacher et al likewise demonstrated that PAO restored abduction-adduction motions, but that study differed in that it showed a change in abduction (from 88 ± 4° to 57 ± 14°, p < 0.001) that was larger than the change in adduction (from 41 ± 13° to 48 ± 14°, p = 0.029) only in the neutral position 39 . Yoshimoto et al recently analyzed squatting kinematics in patients with dysplasia after treatment with PAO using in vivo image registration, showing reduced flexion and abduction postoperatively 46 . Overall, the difference between the changes in abduction and adduction range of motion in the present study suggests that the capsule plays a role in stabilizing the hip and protecting against edge loading.…”
Section: Discussionmentioning
confidence: 99%